Periodontal-Restorative Interrelationships : Ensuring Clinical Success. (Wiley-Blackwell, 2011)
Even with the option of dental implants, periodontists, restorative dentists,?and general dentists alike continue to treat patients' natural teeth on a day-to-day basis. Procedures including crown lengthening surgery, furcation treatment, mucogingival therapy, and tooth restoration are essential treatment regimes requiring multifaceted expertise. Periodontal-Restorative Interrelationships: Ensuring Clinical Success provides guidelines for comprehensive treatment planning, and features step-by-step clinical instruction for periodontal and restorative procedures from beginning to end. As.